Pengaruh Label Halal, Kesadaran Halal, Iklan, dan Celebrity Endorser terhadap Minat Pembelian kosmetik melalui variabel Persepsi sebagai Mediasi (Studi Pada Civitas Akademika Universitas Muhammadiyah Ponorogo) - Premi Wahyu Widyaningrum (UNIVERSITAS PGRI MADIUN, 2019)
Halalness is the main point for Muslims to worship so that people are always on the right path, besides that the halal is stated in the hadith and Al-Quran. Likewise with the interest of consumers trying cosmetics, because cosmetics have shifted from complement to necessity for some groups. Not infrequently, cosmetics are a primary need for monthly shopping. Products that have religious elements, such as cosmetics with halal labels and religious imagery, of course, require celebrities who have a personal and good impression of Muslim women. This will give a positive perception on the minds of consumers then it will cause stimuli to give interest in buying the product. The purpose of this study is to measure how much consumers are aware of consuming halal products, especially the academic community of Muhammadiyah Ponorogo University. This research was conducted at the Muhammadiyah Ponorogo University with a population of academics who are consumers of halal cosmetics. The research location is right on Jl. Budi Utomo no 10 Ponorogo. The sampling technique used a systematic random sampling method, with a sample size of 100 people. The data obtained will be analyzed using the GSCA analysis tool. The results showed that the use of Halal Labels, Halal Awareness, Advertising, and Celebrity Endroser appropriately, effectively and efficiently would provide a large stimulus to Consumer Perceptions in Purchase Intention.Keyword : Halal Awareness, Advertising, Celebrity Endroser, Perceptions, Purchase Intention